Quantitative electroencephalography interpretation of human brain activity after COVID-19 before and after Sudarshan Kriya Yoga - Kopańska, Marta; Kuduk, Barbara; Łagowska, Anna; Mytych, Wiktoria; Muchacka, Renata; Banaś-Za̧bczyk, Agnieszka (Frontiers in Human Neuroscience, 2022)
The COVID-19 pandemic has affected the entire world. SARS-CoV-2 virus is wreaking global havoc leading to serious health problems and even death. The purpose of this study is to present the brainwave variability pattern using QEEG after exposure to COVID-19 and to introduce the subject of Sudarshan Kriya Yoga (SKY) based breathing therapy. QEEG is one of the basic neurological examinations through which we can compare the changes in the nervous system after SARS-CoV-2 virus infection and observe the variation of brainwave frequencies with breathing technique.